Czy mówiąc "prostszym językiem", mówimy prościej? Formalnie narzędnikowe frazy charakteryzujące mówienie - Emilia Kubicka (Ksiegarnia Akademicka Publishing, 2018)
Do We Speak Simpler when Using a Simpler Language? Formally Instrumental Phrases which Characterize Speech The paper describes the connectivity and the meaning of the formally instrumental phrase językiem (jakimś)/(czyimś) which co-occurs with the metatextual mówiąc. Depending on the filling of the valence spot, it can fulfill different functions: a) indicating the choice of the best code or register for the given communicative intent, b) indicating the source of a cited statement, c) informing how to interpret, according to the speaker, what has been said previously in the text. As is the case with other formally instrumental phrases counted as adverbials, here too a regular substitution of those forms with adverbial phrases cannot be observed. The restrictions, however, are probably not of lexical nature (the lack of the appropriate adverbials or adverbial constructions); rather, they result from the fact, that the meaning of the noun is relevant (the meaning of mówiąc slangiem cyklistów is different as jak cykliści). Sometimes there can be also observed a semantic emancipation of some formally instrumental forms (innymi słowy, (jednym) słowem).